A comprehensive analysis of immune infiltration in the tumor microenvironment of osteosarcoma. (13th July 2021) - Yang, Hao; Zhao, Liang; Zhang, Yang; Li, Fang‐Fang
Abstract: Background: Even though immunotherapy has been an effective treatment for solid tumors, its efficacy in osteosarcoma remains sub‐optimal. It is therefore imperative to understand the complex tumor microenvironment (TME) of osteosarcoma to facilitate the development of immunotherapies against this cancer. Methods: The mRNA expression profiles of osteosarcoma tissues were downloaded from The Cancer Genome Atlas (TCGA) database. Next, the ssGSEA, MCP‐counter, CIBERSORT, and Xcell algorithm analyses were performed to characterize the tumor microenvironment of osteosarcoma tissues. The tumor tissues were divided into inflammatory and non‐inflammatory. A comprehensive assessment of immune cell infiltration in osteosarcoma tissues was then performed. Sub‐group analysis of immune cell infiltration between men and women patients with osteosarcoma was also carried out. Results: The results revealed that the infiltration of immune cells including activated B cell, activated CD8 T cell, CD56dim natural killer cell, and cytotoxic lymphocytes cells, in osteosarcoma tissues was higher in male than in female patients. Based on the infiltration profile of different immune cells, the osteosarcoma tissues were grouped into four clusters. The four clusters were further divided into hot and cold tumors. The differently expressed genes (DEGs) between cold and hot tumors were mainly associated with the activation and regulation of immune response. Additionally, a neuronal pentraxin (NPTX2) expression which was upregulated in cold tumors was found to be negatively correlated with the expression of CD8a Molecule (CD8A), Granzyme B (GZMB), and Interferon Gamma (IFNG). NPTX2 decreased CCL4 secretion. Knockdown of NPTX2 in osteosarcoma cells inhibited tumor growth and increased tumor cell apoptosis. Moreover, a prognosis prediction model of osteosarcoma was constructed and validated in patients receiving immunotherapy using external data. Conclusions: To the best of our knowledge, this is the first study to characterize the infiltration of immune cells in osteosarcoma tissues from patients receiving immune infiltration therapy. Abstract : We comprehensively analyzed the possible mechanism of the difference in the immune infiltration of the tumor microenvironment of osteosarcoma, screened out the hub gene set that affects immune infiltration, and verified the survival.